Peran self-esteem sebagai mediator dukungan sosial teman dan keluarga terhadap gangguan psikologis pada mahasiswa - Prasetio, Clement Eko; Triwahyuni, Airin (Persona:Jurnal Psikologi Indonesia, 2021)
Abstract Students face many demands, both academically and psychologically. The number of demands makes students vulnerable to psychological disorders. Psychological disorders have a negative impact on the lives of students and also the people around them. Students who have social support are thought to have a lower risk of experiencing psychological disorders. This study aims to determine the role of self-esteem as a mediator between social support and psychological disorders. Research participants were 376 students from second to fourth year in a Faculty at X University. Research measurement tools which were used in this study, consist of Perceived Social Support Friends (α =0,860) and Family (α =0,902); Rosenberg Self-Esteem's Scale (α =0,871); and Self-Report Questionnaire (α =0,860). Simple mediation analysis using SPSS, especially PROCESS were used for analyzing the results. The results of the analysis show that self-esteem can mediate the relationship between social support from friends and family with psychological disorders in undergraduate students. The implications of the research results are also discussed. Keywords: College Student; Mediation; Perceived Social Support; Psychological Problems; Self-Esteem Abstrak Mahasiswa menghadapi banyak tuntutan, baik secara akademik maupun psikologis. Banyaknya tuntutan membuat mahasiswa rentan mengalami gangguan psikologis. Gangguan psikologis berdampak negatif bagi kehidupan mahasiswa dan juga orang-orang disekitarnya. Mahasiswa yang memiliki dukungan sosial diduga memiliki risiko lebih rendah untuk mengalami gangguan psikologis. Penelitian ini bertujuan untuk mengetahui peran self-esteem sebagai mediator antara dukungan sosial dengan gangguan psikologis. Sebanyak 376 mahasiswa angkatan 2016-2018 pada sebuah fakultas di Universitas X menjadi partisipan penelitian. Alat ukur penelitian yang digunakan dalam penelitian ini adalah Perceived Social Support Scale Friend (α =0,860) and Family (α =0,902); Rosenberg Self-Esteem’s Scale (α =0,871); dan Self-Report Questionnaire-20 (α =0,860). Teknik analisis yang digunakan adalah analisis mediasi sederhana dengan menggunakan SPSS, khususnya PROCESS. Hasil analisis menunjukkan bahwa self-esteem dapat memediasi hubungan antara dukungan sosial teman dan keluarga dengan gangguan psikologis pada mahasiswa. Implikasi dari hasil penelitian juga ikut serta dibahas. Kata Kunci: Dukungan Sosial; Gangguan Psikologis; Self-Esteem; Mahasiswa; Mediasi